Preferences of physicians for treatment-related toxicity vs. recurrence in melanoma (GERMELATOX-A): the doctors’ perspective - Kähler, Katharina C.; Gutzmer, Ralf; Angela, Yenny; Livingstone, Elisabeth; Lodde, Georg; Meiss, Frank; Rafei-Shamsabadi, David A.; Weyer-Fahlbusch, Sera S.; Nashan, Dorothée; Loquai, Carmen; Hassel, Jessica C.; Sachse, Michael M.M.; et al. (Journal of Cancer Research and Clinical Oncology, 2024)
Introduction: Adjuvant treatment with immune checkpoint inhibitors, such as PD1-antibodies (ICI) ± CTLA4-antibodies (cICI) or targeted therapy with BRAF/MEK inhibitors (TT), has shown a significant improvement in disease-free survival (DFS) for high-risk melanoma patients. However, due to specific side effects, the choice of treatment is often influenced by the risk of toxicity. Therefore, the role of physicians in treatment decisions of patients is crucial. This study investigated for the first time in a multicenter setting the attitudes and preferences of dermatooncologists in Germany and Switzerland regarding adjuvant treatment with (c)ICI and TT. Methods: In the GERMELATOX-A study, 108 physicians (median age: 32 yrs, 67.6% female) from 11 skin cancer centers were surveyed to rate typical side effect scenarios of (c)ICI and TT treatments and then compared to patients’ ratings evaluated in a previous analysis from the same centers. The scenarios described mild-to-moderate or severe toxicity and included melanoma relapse leading to death. The physicians were asked about the level of side effects they would tolerate in exchange for a reduction in melanoma relapse and an increase in survival at 5 years. Results: The preferences of physicians and patients revealed significant differences regarding adjuvant melanoma treatment with (c)ICI and TT (p < 0.05). Compared to patients, physicians tend to value a melanoma relapse less severe, according to a visual analog scale. They were also less threatened by all scenarios of side effects during adjuvant treatment with (c)ICI or TT, compared to patients. Physicians required lower risk reductions for disease-free survival (DFS) and overall survival (OS) for both ICI and TT and their drug-related side effects to accept these treatments. In case of severe side effects, physicians required similar 5-year DFS rates for ICI and TT (60–65%), while patients needed a 15% improvement of 5-year DFS for ICI compared to TT (80%/65%). For survival, physicians expected an OS improvement of + 10% for all three treatment modalities, whereas patients required a higher increase: + 18–22% for ICI and + 15% for TT. Conclusion: Our study highlights the importance of understanding the patient’s perspective and a potential difference to the doctor’s view when making decisions about adjuvant melanoma treatment with (c)ICI and TT, especially as these treatments are increasingly being implemented in earlier stages.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Adjuvant treatment; Melanoma; Physician preferences; Treatment toxicity